The Effect of Nanoparticles on Drug Distribution in The Mathematical Model of Blood Flow - Norasia, Yolanda; Nisa, Ajeng Oxa; Sumardi, Sitti Rosnafi'an (Universitas Islam Lamongan, 2024)
This research examines the influence of nanoparticles in the distribution of drugs in healthy blood flow on linear, angular velocity and blood temperature. Construction and simplification of a blood flow model based on boundary layer equations, dimensionless variables, stream functions, and similarity variables. The initial step is to establish a dimensional blood flow model. Using dimensionless variables, the equation is simplified into a dimensionless equation. A similarity equation is generated by converting the non-dimensional equation. The nanoparticles used are . At the linear velocity and temperature of blood flow is in the highest position. At the angular velocity of blood flow, the position of blood flow with nanoparticles is in the uppermost position. This research is used to estimate the velocity and temperature of blood flow with the influence of nanoparticles as drug distribution.